Bio-Energy during Finals: Stress Reduction for a University Community. Issue 4 (1st October 2016) - Running, Alice; Hildreth, Laura
ABSTRACT: To re-examine the effectiveness of a bio-energy intervention on self-reported stress for a convenience sample of university students during dead week, a quasi-experimental, single-group pretest-posttest design was used. Thirty-three students participated, serving as their own controls. After participants had consented, a 15-min Healing Touch intervention followed enrollment. Self-reported stress was significantly reduced after the bio-energy (Healing Touch) intervention. Bio-energy therapy has shown to be beneficial in reducing stress for students during dead week, the week before final examinations. Further research is needed.